2022
DOI: 10.1109/lsp.2022.3210834
|View full text |Cite
|
Sign up to set email alerts
|

Code Optimization and Angle-Doppler Imaging for ST-CDM LFMCW MIMO Radar Systems

Abstract: We consider code optimization and angle-Doppler imaging for slow-time code division multiplexing (ST-CDM) linear frequency-modulated continuous-wave (LFMCW) multipleinput multiple-output (MIMO) radar systems. We optimize the slow-time code via the minimization of a Cramér-Rao Bound (CRB)-based metric to enhance the parameter estimation performance. Then, a computationally efficient RELAX-based algorithm is presented to obtain the maximum likelihood (ML) estimates of the target angle-Doppler parameters. Numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Subsequently, [27] derived the closed-form expression for the Cramér-Rao bound (CRB) and demonstrated that the subspace-based methods can be utilized without any modification when using a uniform linear array (ULA). In [28,29], the authors performed a CRB study in PMCW MIMO radar. To address the channel estimation problem, a gridless atomic norm based approach was proposed in [30].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, [27] derived the closed-form expression for the Cramér-Rao bound (CRB) and demonstrated that the subspace-based methods can be utilized without any modification when using a uniform linear array (ULA). In [28,29], the authors performed a CRB study in PMCW MIMO radar. To address the channel estimation problem, a gridless atomic norm based approach was proposed in [30].…”
Section: Introductionmentioning
confidence: 99%